Palladium‐Catalyzed Allylic Alkylation of Aldimine Esters with Vinyl‐Cyclopropanes to Yield α, α‐Disubstituted α‐Amino Acid Derivatives. Issue 22 (4th October 2019) - Wang, Jiahua; Dai, Zonghao; Xiong, Cheng; Zhu, Jin; Lu, Jinrong; Zhou, Qingfa
Abstract: A synthetically useful approach for the synthesis of functionalized α, α‐disubstituted α‐amino acid derivatives via palladium‐catalyzed 1, 7 addition of readily available aldimine esters to vinylcyclopropanes is reported. This methodology was operated under mild conditions, affording α‐allylic α‐amino esters in good to excellent yields and excellent regio‐ and stereoselectivity. This transformation displays broad functional‐group tolerance and enantioselective allylic alkylation has also been realized using a chiral phosphine ligand to provide the desired product. Abstract :